Regulatory changes and their Impact on Tax compliance: An overview of Finance Act 2023 - Aliyu, Umar (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
The aim of this study is to evaluate and review the regulatory changes and their impact on tax compliance, it is an anthology of the existing literature on finance Act and tax compliance with a view to identifying the gaps to which future literature may be directed within the Nigerian context. The paper discusses the concept of finance Act and its surrounding issues on tax compliance as appraised by different authors. The data used for the study were mainly secondary data from different sources. The researchers critically review related literatures from various secondary sources with a particular emphasis on Finance Act 2023, as well as other Nigerian tax legislations. The secondary sources were complemented by the personal observation of Nigerian tax system in Nigeria by the researchers. The study revealed mixed findings on the extent to which finance Act and other financial regulations impact on the economy. The study also concludes that, the factors determining financial regulations are not fixed, and vary from one jurisdiction to another. The study therefore recommends that, from the theories that relates to financial regulations, there shall be a unified theory that amalgamates the existing theories; and that which will be amenable to the ever-changing reporting environment.